2002
DOI: 10.1172/jci200215518
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that fibroblasts derive from epithelium during tissue fibrosis

Abstract: Interstitial fibroblasts are principal effector cells of organ fibrosis in kidneys, lungs, and liver. While some view fibroblasts in adult tissues as nothing more than primitive mesenchymal cells surviving embryologic development, they differ from mesenchymal cells in their unique expression of fibroblast-specific protein-1 (FSP1). This difference raises questions about their origin. Using bone marrow chimeras and transgenic reporter mice, we show here that interstitial kidney fibroblasts derive from two sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
245
1
11

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(268 citation statements)
references
References 50 publications
11
245
1
11
Order By: Relevance
“…This is in agreement with the report by Iwano et al that BMCs can differentiate into renal interstitial fibroblast (22). Renal IRI is accompanied by inflammatory cell infiltration, and the inflammation subsides after 10 days (42).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the report by Iwano et al that BMCs can differentiate into renal interstitial fibroblast (22). Renal IRI is accompanied by inflammatory cell infiltration, and the inflammation subsides after 10 days (42).…”
Section: Discussionsupporting
confidence: 93%
“…There is increasing evidence that circulating stem cells can enter the kidney and differentiate into renal cells after various injuries. We and others have shown that bone marrow cells (BMCs) can differentiate into tubular epithelial cells, glomerular endothelial cells, podocytes, mesangial cells, and renal interstitial cells (16)(17)(18)(19)(20)(21)(22). After transplanting hematopoietic stem cells isolated from male Rosa26 mice, we detected cells expressing β-gal in the renal tubules in female wild-type mice that had renal IRI.…”
Section: Introductionmentioning
confidence: 81%
“…Indeed, adult neuronal stem cells display morphological and molecular characteristics of differentiated astrocytes (25). In addition, de-differentiation of renal epithelial cells into myofibroblasts, a long-suspected process (26), has recently been demonstrated conclusively (27), and it may be postulated that, as during limb and tail repair in some amphibians (28), de-differentiation of renal epithelial cells after organ injury may be followed by cell proliferation and re-differentiation into multiple cell types (29). Thus, terminally differentiated kidney cells may well be functioning as pluripotent stem cells during organ maintenance and repair.…”
Section: Figurementioning
confidence: 98%
“…Another potential origin for new, terminally differentiated kidney cells during kidney repair may be the mesenchymal cells that develop during the epithelial to mesenchymal transition, which occurs during renal injury (27), as found in other systems (28). A surprising recent finding has been the discovery that some of the new renal cells are derived from extrarenal cells.…”
Section: Figure 10mentioning
confidence: 99%
“…Iwano et al(2002) found that a large proportion of interstitial fibroblasts were actually originated from local TEMT during renal fibrogenesis. In the process of TEMT, tubular epithelial cells lose epithelial cell marker E-cadherin and de novo express myofibroblast cell marker α-SMA (Liu, 2004).…”
Section: Discussionmentioning
confidence: 98%